The Use of Neodymium-Doped Yttrium Aluminum Garnet Laser for Treatment of Hypertrophic Port-Wine Stain - Brittany Miles; Andrew Armenta; James Mackey (Case Reports in Dermatological Medicine)
Port-wine stains (also called nevus flammeus) are congenital malformations of the capillaries and postcapillary venules. They occur in 0.1–2% of newborns without sex predilection. Although PWS lesions are flat early in life, with age, they become hypertrophic and darker. Pulsed dye laser therapy is the standard of care for treating these lesions, although other laser wavelengths have been utilized with varying degrees of success. We present the case of a gentleman with a hypertrophic PWS who had an excellent response to Nd:YAG laser treatment. The increased tissue penetration of longer laser wavelengths may be of benefit to patients with hypertrophic PWS, and further research into this concept is warranted.